POLITIK ISLAM SEBAGAI SARANA MEWUJUDKAN KESEJAHTERAAN SOSIAL - Ach. Fawaid Ansori; Nasrul Syarif; Mavatih Fauzul ‘Adziima (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Islamic politics is viewed as a means to realize social welfare by positioning political authority as a divine trust (amānah ilāhiyyah), rather than merely an arena for competing over power and positions. Politics is understood as an effort to manage the affairs of the ummah with justice, dignity, and a strong orientation toward public interest (maṣlaḥah). Social welfare in Islam encompasses not only material aspects but also spiritual, moral, social, and cultural dimensions, in line with the maqāṣid al-sharī‘ah, which emphasize the protection of religion, life, intellect, lineage, and property. Using library research and content analysis methods, this study demonstrates that the fundamental principles of Islamic politics—such as justice (‘adl), consultation (shūrā), equality (al-musāwah), trustworthiness (amānah), responsibility (mas’ūliyyah), and enjoining good and forbidding evil (amr bi al-ma‘rūf wa nahy ‘an al-munkar)—as well as socio-economic instruments like zakāt, infāq, ṣadaqah, waqf, the prohibition of usury (ribā), natural resource management, independent judiciary, and educational policies, play significant roles in reducing poverty and structural inequality.